Simulation of Lateral Distribution Function of Cherenkov Light in Extensive Air Showers for Yakutsk Array (Journal of the College of Basic Education, 2023)
The simulation of Cherenkov light Lateral distribution function (LDF) for primary particles like primary protons, Iron nuclei, Oxygen, Nitrogen, Calcium, Neutron and Argon have been performed with CORSIKA code for conditions and configuration of Yakutsk array in the energy range 1014-1016 eV for four zenith angles 0o, 5o, 10o and 15o. The results of this simulation are compared with the measurements of Yakutsk array for the same particles and energyrange